El secreto, el mal y el miedo El género criminal rehecho en 2666 de Roberto Bolaño - Pluta, Nina (Romanica Silesiana)
Roberto Bolaño, a Chilean author who passed away in 2003, tackles the problem of evil using a criminal convention which underwent profound changes in the second half of the 20th century. One of its most popular types nowadays is the metaphysical detective story, in which the investigation is complicated by various cognitive riddles reflecting the Postmodernist intellectual disputes. Bolaño’s last novel — which is the subject of this article — is titled 2666 and was published in 2004. It is a metaphysical detective story set in Northern Mexico which focuses on the country’s current social problems. In the novel, crime and evil are not a metaphor for the human intellectual cognition, as they are tightly connected with the political injustice that main characters experience on a day to day basis. Key words: Postmodern fiction, Spanish-American fiction, detective genre, the evil.